A emergência e o desenvolvimento do uso de operadores argumentativos na escrita de crianças no ciclo de alfabetização - Neves, Jailson da Silva (2021)
This research aimed to investigate, through a longitudinal study, the emergence and development of the use of argumentative operators in the writing of children in the literacy cycle of elementary school. The specific objectives were: to investigate the use of argumentative operators employed in children's texts, mapping when and which ones initially appear in children's writing; analyze the development of the use of argumentative operators over a two-year period (the literacy cycle in elementary school), associating it with other linguistic knowledge of the child revealed in the texts and possibly used to replace the operators; describe the relationship between the argumentative operators used and the argumentativeness of the analyzed children's texts. As theoretical foundation, this work adopts the assumptions of the Theory of Argumentation in Language (DUCROT, 1972, 1990) that argumentation is inscribed in the language and that the argumentative operators have the function of guiding the ways of the discourse (KOCH, 2009a, 2009b, 2011). It was used the classification of argumentative operators created by Koch (2009a). 52 texts written by 13 students from the literacy cycle were analyzed. Each child wrote four versions of the Little Red Riding Hood story over two years. As a result of the analyses, it was concluded that: argumentative operators appear in the first texts of the learning phase of writing; throughout the literacy cycle, children learn new argumentative operators and start to use them in spoken and written language; children employ argumentative operators that establish the relations of conjunction, counterjunction, explication, conclusion and confirmation; the texts are loaded with argumentative contexts; the use of argumentative operators contributes to argumentativeness in children's texts, guiding the discourse and strengthening textual cohesion.